“Investigating Whether Efficient Market Hypothesis Could be Beaten by Careful Implementation of Technical Analysis“ - Kuntsevich, Kirill (2014)
Abstract One of the fundamental issues of Efficient Market Hypothesis is that participants of financial markets cannot achieve abnormal returns by analyzing past prices. Conversely, technical analysis is based on the analysis of past prices. In order to obtain competitive advantage technical analysis examines graphs and gives predictions about future behaviour of prices for financial instruments. Both fields are broadly discussed and provide a number of works confirming their efficiency. The central element of this work is a research done with the purpose to find out which approach is more valuable for modern financial markets (technical analysis or efficient market hypothesis). This main aim consists of three smaller goals, which are reached by this work. These aims are formulated below and also include a brief explanation of further chapters of the work. The aims of this study: 1) To evaluate whether at least a theoretical possibility of obtaining abnormal returns with the use of technical analysis exists on modern financial markets; With the purpose of understanding whether technical analysis really provides an opportunity not to be simply profitable but to overrun the whole market, the most common indicators of all the main types are tested. The rules according to which every indicator is used are strictly defined and exclude non-objectivity in the estimation of results which are relatively common problems in the examined field. All the features, such as: amount of invested funds, interest rates, dividends, levels of margin, commission costs and others are clearly specified and are taken into account. Moreover, the tests include most liquid stocks of three financial markets of different efficiency levels and also demonstrate the impacts of these levels on the obtained results. The features of additional risks and obstacles preventing abnormal profitability of strategies are discussed. 2) To estimate the level of efficiency of considered financial markets (MICEX, FTSE 100 and S&P 500) and to check if obtained results match with previous results; In order to confirm or deny the previous part and estimate the level of efficiency of the examined markets a number of econometrician tests are carried out. The validity of such approach is that these tests are implemented in a completely separate way from the previous part and provide an opportunity to test different versions of forecasting, which is also implemented further. 3) To test the forecasting ability of technical analysis and to investigate whether in close-to-real conditions careful use of technical analysis allows to overrun the market and to beat the fundamental issues of Efficient Market Hypothesis. The first tests were aimed at understanding whether technical analysis allows to overbeat the market return (against foundations of Efficient Market Hypothesis). However, this part tests the forecasting ability of technical analysis. Additionally, it is focused around ways of achieving abnormal returns. All previously discussed conditions remain the same (costs, rates, indicators and others) and the technique that allows to obtain such returns in the almost real market conditions is explained and tested. Finally, this part proves that careful implementation of discussed 3 techniques allows one to expect returns higher than the growth of the examined markets.